SARM1 Suppresses Axon Branching Through Attenuation of Axonal Cytoskeletal Dynamics - Ketschek, Andrea; Holland, Sabrina M.; Gallo, Gianluca (Frontiers in Molecular Neuroscience, 2022)
Axon branching is a fundamental aspect of neuronal morphogenesis, neuronal circuit formation, and response of the nervous system to injury. Sterile alpha and TIR motif containing 1 (SARM1) was initially identified as promoting Wallerian degeneration of axons. We now report a novel function of SARM1 in postnatal sensory neurons; the suppression of axon branching. Axon collateral branches develop from axonal filopodia precursors through the coordination of the actin and microtubule cytoskeleton. In vitro analysis revealed that cultured P0-2 dorsal root ganglion sensory neurons from a SARM1 knockout (KO) mouse exhibit increased numbers of collateral branches and axonal filopodia relative to wild-type neurons. In SARM1 KO mice, cutaneous sensory endings exhibit increased branching in the skin in vivo with normal density of innervation. Transient axonal actin patches serve as cytoskeletal platforms from which axonal filopodia emerge. Live imaging analysis of axonal actin dynamics showed that SARM1 KO neurons exhibit increased rates of axonal actin patch formation and increased probability that individual patches will give rise to a filopodium before dissipating. SARM1 KO axons contain elevated levels of drebrin and cortactin, two actin regulatory proteins that are positive regulators of actin patches, filopodia formation, and branching. Live imaging of microtubule plus tip dynamics revealed an increase in the rate of formation and velocity of polymerizing tips along the axons of SARM1 KO neurons. Stationary mitochondria define sites along the axon where branches may arise, and the axons of SARM1 KO sensory neurons exhibit an increase in stationary mitochondria. These data reveal SARM1 to be a negative regulator of axonal cytoskeletal dynamics and collateral branching.